Erythrodermiaichtyosisformis congenital – A case report - Ambarkova, Vesna; Zisovska, Elizabeta; Kalcev, Goce; Misevski, Josif; Damevska, Katerina; Ismaili, Bashkim; Ambarkov, Jovan (Journal of Orofacial Research, 2019)
Non-bullous congenital ichthyosi-form erythroderma is an autosomal recessive congenital keratinization disorder. We present the only one registered case of congenital non-bullous ichthyosiformerythroderma in North Macedonia. Our patient now is a 29-year old man from Gostivar. He was born with low birth weight and a low Apgar score (5/7). After birth, the skin was so cracked, that there were bleeding in certain places. Furthermore, the entire body, especially the head, was covered with yellow-green scales of varying size, which were firmly attached to the substrate. There was no history of similar or same illness in the family. Little is known about the oral manifestations of this disorder. The prognosis is variable. The disease has a strong impact on the quality of life due to altered physical appearance, problematic symptoms and treatment restrictions.